Puteri Sa'dung's Thinking in Hikayat Seri Kelantan: (Pemikiran Puteri Sa'dung dalam Hikayat Seri Kelantan) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2018)
This research focuses on the aspect of women's intellectuality through the character of Puteri Sa'dung in Hikayat Seri Kelantan (HSK) this historiographical text, which indirectly exemplifies the thinking of the Malays. The intellectual aspect is analysed using the Sistem Pemikiran Bersepadu 4K Theory (SPB4K) propounded by Yusof Hassan. The intellectual aspect clearly shows the thinking of the Malays of old, especially that of women who had to shoulder the burden of the leadership of a kingdom. The findings of the study prove that integrated thinking, that is, spiritual thinking, unequalled thinking, scientific thinking and creative thinking are all evidenced in this work, and shed light on the thinking of the character under study. All four types of thinking display the special nature of the character's relationship with Allah SWT and with other people, as well as her problem-solving skills. The SPB4K Theory is found to be a suitable for studying traditional texts.Keywords: intellectuality, Malay thinking, integrated thinkig, historiography.